Public finance investment : how mutual funds in government stock influence investment activity - Kgomo, D. M. (l International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference, 2020)
Investment has been recognized as one of the most volatile expenditure components over the business cycle. Investment activity should therefore be convenient, practical and efficient as investment activity can enhance economic growth. This study aims to investigate how mutual funds in government stock influence investment activity. The study made use of panel unit root test, panel autoregressive distributed lag model (PARDL), panel cointegration tests, Engle-Granger causality test, impulse response functions and variance decomposition tests. The panel unit root tests confirmed different orders of cointegration. Panel cointegration tests, where one lag was used, indicated the presence of a long-run relationship among investment activity and mutual funds. Investment activity is positively impacted by mutual funds in the long run as suggested by the PARDL model. The Engle-Granger casualty test indicates a unidirectional causality from investment activity to government stock on corporations; as well as from government stock on bonds to liquid assets. The impulse response function test showed the impulse percentage of fluctuation that the variables did contribute to each other, from various periods in the short including the long run. The results showed a long run relationship between the variables as they move together in the long run and mutual funds having a positive effect on investment activity. It is therefore recommended that mutual fund policymakers should make policies that will lead to financial stability and increase the performance of financial institutions. These policies should be able to help financial institutions in making investment decisions that will further benefit them and the country's economy not only in the short term but also in the long term. A critical evaluation is needed to avoid investment shocks, instability of investment activity, instability of financial markets and the economy as a whole. Keywords: Engle-Granger causality test, Investment activity, Mutual funds, Panel Autoregressive Distributed Lag
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Engle-Granger causality test; Investment activity; Mutual funds; Panel Autoregressive Distributed Lag; Investments; Mutual funds; Economic development